MODEL PENDIDIKAN ANAK KELUARGA NABI IBRAHIM DAN KELUARGA LUQMAN AL-HAKIM - Muhammad Taufiqur Rahman; Bambang Harmanto; Katni Katni (Universitas Muhammadiyah Ponorogo, 2019)
Children are the best gift from God for a family. Children must get an obligation to educate and find the best place to be educated with the right learning method. The best education is education that is in harmony with the education taught in the Qur'an and Sunnah, but the model of children's education has not yet become a serious concern, both among Islamic academics and parents. This research uses qualitative research and uses library research methods. Then the writer analyzes the data with content analysis. Because this theory uses the reference of the Qur'an directly, then the first source of the Qur'an. Then from the sources of the other books that included education on the children of the Ibrahim and Luqman families. In the education process, the family uses a contextual learning model. In the contextual learning model contains principles that are in accordance with the family education. And found the material taught by Prophet Ibrahim to his children as follows: Aqidah Education, Moral Education, prayer education. And the method used is the method of dialogue, exemplary, advice, targhib wa tarhib, argument. While the material in Luqman education is tauhid education, devoting to parents, doing good deeds, and worshiping. And using exemplary, repetition and advice methods. The material equations in the two families are monotheism and morality. And the difference is the material of prayer and doing good. The equation of the method of both is advice and exemplary. The differences are repetition, dialogue and argument.